Barriers and facilitators to implementing continuous quality improvement programs in colonoscopy services: a mixed methods systematic review - Candas, Bernard; Jobin, Gilles; Dubé, Catherine; Tousignant, Mario; Abdeljelil, Anis Ben; Grenier, Sonya; Gagnon, Marie-Pierre (Endoscopy International Open, 2016)
Background and aim: Continuous quality improvement (CQI) programs may result in quality of care and outcome improvement. However, the implementation of such programs has proven to be very challenging. This mixed methods systematic review identifies barriers and facilitators pertaining to the implementation of CQI programs in colonoscopy services and how they relate to endoscopists, nurses, managers, and patients.Methods: We developed a search strategy adapted to 15 databases. Studies had to report on the implementation of a CQI intervention and identified barriers or facilitators relating to any of the four groups of actors directly concerned by the provision of colonoscopies. The quality of the selected studies was assessed and findings were extracted, categorized, and synthesized using a generic extraction grid customized through an iterative process. Results: We extracted 99 findings from the 15 selected publications. Although involving all actors is the most cited factor, the literature mainly focuses on the facilitators and barriers associated with the endoscopists’ perspective. The most reported facilitators to CQI implementation are perception of feasibility, adoption of a formative approach, training and education, confidentiality, and assessing a limited number of quality indicators. Receptive attitudes, a sense of ownership and perceptions of positive impacts also facilitate the implementation. Finally, an organizational environment conducive to quality improvement has to be inclusive of all user groups, explicitly supportive, and provide appropriate resources.Conclusion: Our findings corroborate the current models of adoption of innovations. However, a significant knowledge gap remains with respect to barriers and facilitators pertaining to nurses, patients, and managers.